2012
DOI: 10.1016/j.molimm.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Oct-1 acts as a transcriptional repressor on the C-reactive protein promoter

Abstract: C-reactive protein (CRP), a plasma protein of the innate immune system, is produced by hepatocytes. A critical regulatory region (−42 to −57) on the CRP promoter contains binding site for the IL-6-activated transcription factor C/EBPβ. The IL-1β-activated transcription factor NF-κB binds to a κB site located nearby (−63 to −74). The κB site overlaps an octamer motif (−59 to −66) which is the binding site for the constitutively active transcription factor Oct-1. Oct-1 is known to function both as a transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It is worth noting that the identified OCT-1 binding site conserved in pigs and humans was previously found by Voleti et al. in 2012 ( 22 ) as a modulator of CRP expression in humans by positional competition with other binding sites in the region.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It is worth noting that the identified OCT-1 binding site conserved in pigs and humans was previously found by Voleti et al. in 2012 ( 22 ) as a modulator of CRP expression in humans by positional competition with other binding sites in the region.…”
Section: Discussionmentioning
confidence: 65%
“…A more detailed analysis of this region revealed the presence of a putative enhancer element conserved between human and cow species, and containing transcription factor binding sites for STAT3, C/EBP, NF-kB, HNF4α, OCT-1 FOXA1 and FOXA2. These transcription factors have been widely described as being required for the constitutive expression and/or acute phase induction of CRP ( 21 , 22 , 56 59 ). Remarkably, a recent study performed in humans identified an enhancer (E1) located 37.7 Kb upstream of the CRP promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gastric cancer cells, Oct1 is recruited to the CDX2 promoter but loses its ability to activate transcription, highlighting its complex regulatory role [ 34 , 35 ]. Additionally, Oct-1 inhibits Slc7a11 and CRP gene expression by binding to their promoters [ 36 , 37 ]. These insights suggest that the protective effect of the TLR4 rs1927914G allele in colon cancer may result from enhanced Oct-1 binding, leading to reduced TLR4 expression and decreased cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the concentration of CRP in circulation increases rapidly within hours of an inflammatory stimulus due to its increased hepatic synthesis under transcriptional and post-transcriptional control (Bode et al, 2012;Kim et al, 2015;Singh et al, 2007;Voleti and Agrawal, 2005;Voleti et al, 2012;Zhang et al, 1995). CRP has also been shown to be deposited at localized sites of inflammation such as at atherosclerotic lesions, in the joints of arthritic patients, and surrounding the amyloid plaque deposits in patients with Alzheimer's disease (Gitlin et al, 1977;Hatanaka et al, 1995;Iwamoto et al, 1994).…”
Section: Introductionmentioning
confidence: 99%